2014
DOI: 10.1007/s40292-014-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Weeks Green Tea Extract Consumption on Blood Pressure, Heart Rate Responses to a Single Bout Resistance Exercise in Hypertensive Women

Abstract: Three weeks of GTE ingestion did not influenced SBP, DBP and HR but may be have a favorable effect on MAP and RPP responses to an acute RE during 1 h recovery of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
1
24
0
3
Order By: Relevance
“…A study by Arazi et al [77] performed on middle-aged women with HT revealed practically the same reduction in BP after resistance training with or without green tea supplementation (Figure 3). There was no significant difference between the placebo and green tea intake groups (500 mg daily = 245 mg polyphenol, 75 mg epigallocatechin gallate, 25 mg caffeine) or placebo (490 mg maltodextrin).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…A study by Arazi et al [77] performed on middle-aged women with HT revealed practically the same reduction in BP after resistance training with or without green tea supplementation (Figure 3). There was no significant difference between the placebo and green tea intake groups (500 mg daily = 245 mg polyphenol, 75 mg epigallocatechin gallate, 25 mg caffeine) or placebo (490 mg maltodextrin).…”
Section: Resultsmentioning
confidence: 63%
“…One study included only men [72], and three included a mixed sample of men and women [70,71,73]. Five studies included only women [74,75,76,77,78]. In total, five studies compared the effect of ST with the NP intervention effect on BP [70,73,74,75,76].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arazi et al 25 supplemented hypertensive women for three weeks prior to the intervention with resistance exercise. The authors showed no changes in PEH, except in mean arterial pressure immediately and 15 minutes after the exercise session.…”
Section: Discussionmentioning
confidence: 99%